The use of e-cigarettes among university students in Malaysia - Wan Puteh S.E.; Manap R.A.; Hassan T.M.; Ahmad I.S.; Idris I.B.; Sham F.M.; Yu Lin A.B.; Soo C.I.; Pakri Mohamed R.M.; Mokhtar A.I.; Zakaria H.; Lee J.; et al. (International Society for the Prevention of Tobacco Induced Diseases, 2023)
adult; Article; cigarette smoking; clinical feature; controlled study; coughing; cross-sectional study; demography; dizziness; female; headache; human; Malaysia; male; priority journal; self concept; semi structured interview; sex difference; smoking cessation; social aspect; social behavior; university student